(untitled) (Journal of the College of Basic Education, 2022)
This study was conducted to demonstrate the effect of adding powder, rosemary, cumin, single or combination, and different rates in some qualitative and organoleptic qualities of meat minced inventory for a period of 0, 3, 6, 9 and 12 days at a temperature of 4°C.meat minced part equal weights to six transactions as follows: the first treatment of comparison C (meat minced non treatment) second treatment C1 and third C2 add rosemary single to meat minced by 0.75 and 1.5%, respectively, the fourth treatment C3 and fifth C4 add cumin single at a rate of 0.75 and 1.5%, respectively, sixth and treatment C5 percentage added powdery These vegetables were collectively 0.75% each. The following results were obtained: a gradual decline evident in the logarithm of the total number of each of the total aerobic bacteria and coliform bacteria and Staphylococcus aureus and psychrotrophic when you add powdery vegetarian rosemary, cumin collectively, It was also noted a rise in pH, and a significant decrease in the peroxide value (PV) and values free fatty acids (FFA) compared with the control treatment. Sensory evaluation scores rose and appeared significant differences between transactions at a level of probability of P<0.05 compared with treatment-free control of the addendum, where treatment showed C5 to get a significant improvement of the qualities of flavor, juiciness and tenderness and public acceptance.